2015
DOI: 10.1007/s00726-015-2035-9
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation preserves hypothalamic leptin action in normal and protein-restricted mice fed on a high-fat diet

Abstract: Malnutrition programs the neuroendocrine axis by disruption of food-intake control, leading to obesity. Taurine (Tau) is neuroprotective and improves anorexigenic actions in the hypothalamus. We evaluated the hypothalamic gene-expression profile and food-intake control in protein-restricted mice submitted to a high-fat diet (HFD) and Tau supplementation. Mice were fed on a control (14 % protein-C) or a protein-restricted diet (6 % protein-R) for 6 weeks. Thereafter, mice received, or not, HFD for 8 weeks (CH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
2
17
1
1
Order By: Relevance
“…However, the HFD feeding did not promoted an additional effect on NPY mRNA levels in Middle-Age mice. Besides that, it has been shown that the Npy mRNA levels increase after 2 weeks and decrease after 12 weeks of HFD treatment [ 29 , 30 ], demonstrating that chronic exposure to HFD induces NPY mRNA stabilization in the hypothalamus and other mechanisms cold be involved in the body weight gain during the long-term of HFD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the HFD feeding did not promoted an additional effect on NPY mRNA levels in Middle-Age mice. Besides that, it has been shown that the Npy mRNA levels increase after 2 weeks and decrease after 12 weeks of HFD treatment [ 29 , 30 ], demonstrating that chronic exposure to HFD induces NPY mRNA stabilization in the hypothalamus and other mechanisms cold be involved in the body weight gain during the long-term of HFD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the HF pups presented a significant reduction in the food intake. This reduced food intake can be attributed to the high energy density of the HF diet (19•87 v. 15•10 kJ/g (4•75 cal/g v. 3•61 kcal/g)) (37) . Diets containing 30 % or more of energy derived from fat induce satiety in rodents as a result of increased energy intake and efficiency of energy storage (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…A cause for these variant observations was not evident. Studies with mice show that TAU may moderately reduce food intake when consumed in excess (Camargo et al., ). But in the present study, food intake was not significantly affected by dietary TAU concentration (Table ).…”
Section: Discussionmentioning
confidence: 99%